Comprehensive evaluation of preoperative patients with aortic valve stenosis: usefulness of cardiac multidetector computed tomography. Issue 9 (4th May 2007) - Laissy, Jean-Pierre; Messika-Zeitoun, David; Serfaty, Jean-Michel; Sebban, Vincent; Schouman-Claeys, Elisabeth; Iung, Bernard; Vahanian, Alec
Abstract : Background: Preoperative assessment of patients with aortic valve stenosis (AS) relies on the evaluation of AS severity (aortic valve area, AVA) and left ventricular ejection fraction (LVEF) by echocardiography, and of coronary artery anatomy by coronary angiography. Aim: To evaluate the feasibility and accuracy of contrast-enhanced multidetector computed tomography (MDCT), as a single non-invasive preoperative test, for simultaneous evaluation of the AVA, LVEF and coronary status in patients with AS. Methods: 40 consecutive patients with AS scheduled for aortic valve replacement underwent transthoracic echocardiography, electrocardiogram (ECG)-gated MDCT and coronary angiography within a time span of 1 week. Results: MDCT measurements could be performed in all patients. A good correlation but a slight overestimation was observed between mean (SD) AVA measured by MDCT and by echocardiography (0.87 (0.22) vs 0.81 (0.20) cm 2, p = 0.01; r = 0.77, p<0.001). Mean difference between methods was 0.06 (0.15) cm 2 . LVEF measured by MDCT correlated well with, and did not differ from, electrocardiographic measurements (59% (13%) vs 61% (10%), p = 0.34; r = 0.76, p<0.001; mean difference 1% (8%)). Coronary angiography displayed 33 lesions in 13 patients. MDCT correctly identified 26 of these 33 lesions and overestimated three <50% stenosis. On a segment-by-segment analysis, MDCT sensitivity, specificity, positive and negative predictive values were 79%, 99%, 90% and 98%, respectively. For each patient, MDCT had a sensitivity of 85% (11/13 patients), a specificity of 93% (25/27 patients) and positive and negative predictive values of 85% (11/13 patients) and 93% (25/27 patients), respectively. Conclusion: MDCT can provide a simultaneous and accurate evaluation of the AVA, LVEF and coronary artery anatomy in patients with AS. In the near future, with technological improvements, MDCT could achieve an exhaustive and comprehensive preoperative assessment of patients with AS. In addition, for the assessment of AS severity in difficult cases, MDCT could be considered as an alternative to transoesophageal echocardiography or cardiac catheterisation.